2020
DOI: 10.1016/j.neuron.2020.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Rapid 3D Enhanced Resolution Microscopy Reveals Diversity in Dendritic Spinule Dynamics, Regulation, and Function

Abstract: Highlights d Most spinules are short-lived, dynamic, recurrent, and originate near simple PSDs d An elongated stable subset traffics PSD fragments and can form secondary synapses d Spinule subsets are positively regulated by local Ca 2+ transients and kalirin-7 d Neuronal activity induces spinule elongation and contact with distal synapses

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 56 publications
(99 reference statements)
4
28
0
Order By: Relevance
“…Coated pits often are seen at the ends of spinules ( Westrum and Blackstad, 1962 ; Spacek and Harris, 2004 ; Yao et al, 2005 ; Tao-Cheng et al, 2009 ), mediating removal and absorption of spinule ends into the terminal. And recent studies with enhanced resolution 3D light microscopy have confirmed that neuronal activity induces spine-derived spinule elongation ( Zaccard et al, 2020 ).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Coated pits often are seen at the ends of spinules ( Westrum and Blackstad, 1962 ; Spacek and Harris, 2004 ; Yao et al, 2005 ; Tao-Cheng et al, 2009 ), mediating removal and absorption of spinule ends into the terminal. And recent studies with enhanced resolution 3D light microscopy have confirmed that neuronal activity induces spine-derived spinule elongation ( Zaccard et al, 2020 ).…”
Section: Resultsmentioning
confidence: 96%
“…This is especially true for the smaller spinule types of invaginating structures because they are difficult to identify without TEM, and even with standard 2D TEM, the origins of the invaginating structures are often obscure. Today, super-resolution and other specialized light microscopy techniques allow better visualization of these invaginating structures in synapses ( Ueda and Hayashi, 2013 ; Zaccard et al, 2020 ). Moreover, the new wave of 3D EM methods such as focused ion beam-scanning electron microscopy (FIB-SEM) makes tracing of these invaginating structures possible.…”
Section: Introductionmentioning
confidence: 99%
“…To understand the mechanism of this activity-stability correlation, intracellular Ca 2+ is important for spine formation and stability in cortical pyramidal neurons as shown in ex-vivo preparations 29, 30 where spine lifetime was positively correlated with Ca 2+ peak frequency and duration. Chelating Ca 2+ resulted in lower spine formation, spinule number and cumulative lifespan per spine 29 . When we presented short duration odor, the activity-stability correlation was not induced, although this stimulus did shift the cumulative distributions of stable and new spines, but this did not correlate with individual dendritic activity.…”
Section: Discussionmentioning
confidence: 99%
“…When we presented short duration odor, the activity-stability correlation was not induced, although this stimulus did shift the cumulative distributions of stable and new spines, but this did not correlate with individual dendritic activity. As to the cellular machinery of spine maintenance and formation, spine stability and lifetime are also associated with the gain of PSD-95 31 and its expression complexity 29 , respectively, whereas spine removal is often preceded by PSD-95 loss 31, 32 . Although it has been shown that GC PSD-95 puncta stabilize with odor enrichment 17 , suggesting an overall activity-dependence, our current results support a direct relationship between activity and stability.…”
Section: Discussionmentioning
confidence: 99%
“…Neuronal activity induces long lasting structural modifications in synapses to promote changes in synaptic strength. For example, LTP induction results in the enlargement of dendritic spines and the formation of multi-contact synapses (Hruska et al, 2018;Zaccard et al, 2020), including MIS, a unique form of structural synaptic plasticity. Indeed, formation of MIS is associated with NMDAR-dependent LTP (Nikonenko et al, 2003;Hruska et al, 2018).…”
Section: Discussionmentioning
confidence: 99%